Prescribing Patterns of Drugs in Outpatient Department of Paediatrics in Tertiary Care Hospital - Thomas, Lita Susan; Lavanya, Selvaraj; Sudaroli, Murugaiyan; Kumar, George Praveen (Indian Journal of Pharmacy Practice)
Paediatrics differs from adult medicine in many respects. Infants and children suffer from frequent but usually non serious illnesses. Effective medical treatment of paediatric patient is based upon an accurate diagnosis and optimum course of therapy, which usually involves a medication regimen. The aim of the study is to ascertain the disease pattern and drug prescribing pattern for outpatients attending the paediatrics services (OPD) in a tertiary care hospital. A total of 500 prescriptions were collected and analyzed. The average number of drugs per prescription was 3.74±1.02. Upper respiratory tract infection was the most common reason for attending the paediatrics outpatient department [173 patients (34.6%)]. The other common diagnosis were Bronchitis [81 patients (16.2%)], Acute gastroenteritis [28 patients (5.6%)], Fever [22 patients (4.4%)], Asthma [13 patients (2.6%)], Pneumonia [1 patient (0.2%)], others [75 patients (15%)] and Combination [107 patients (21.4%)]. Antibiotics were the most commonly prescribed category followed by NSAIDs. Appropriate drug utilization studies have been found to evaluate whether drugs are properly used and utilized in terms of medical, social and economic aspects.
Keywords: Antibiotics; Department; Drug utilization Outpatients; Paediatrics; Prescription pattern